An Inventory of Ichthyofauna of Kolhapur District - Ghatge, Swapnil Shivajirao; Balaji. R. Kharatmol; Rohit B. Hajare; Krishna D. Patil; Shrikant S. Jadhav (Journal of Indian Fisheries Association, 2024)
There is need of comprehensive systematic updated inventory of fishes available in Kolhapur district for sustainable development of fisheries, aquaculture and ornamental fish industry and more importantly for conservation purpose. Hence, an attempt was made in the present study to provide an inventory of ichthyofauna of Kolhapur district. A systematic and comprehensive review of available literature was made along with collections made by authors and specimens available at Zoological Survey of India, Pune to carry out the Meta-analysis of all the published (both peer reviewed and non-peer reviewed) literature and collections. The present inventory comprises of total 110 fish species belonging to 10 orders 27 families and 62 from Kolhapur district. Cypriniformes is the dominant order represented by 69 species, followed by Silurifomres (22 species), Anabantiformes (5 species), Cyprinodontiformes and Synbranchiformes (3 species each). While Beloniformes, Cichiliformes and Mugiliformes were represented by two species each, Anguilliformes and Gobiiformes were represented by one species each. A list of further 19 species earlier recorded in literature with explanation for its deletion is provided. As per the IUCN Red list of Threatened Species, Sixty Six species assessed as Least Concern, whereas Five species assessed as Data Deficient, Six species as Near Threatened, Eight as Vulnerable and Nine as Endangered (IUCN 2024). Three Species were Not Evaluated, Three Transplanted and Ten Exotic species.  The present work will form a baseline for future studies.